4 - ‘The State of the Continent is Good’: African ‘Foreigners’ and Foreign Direct Investment, Seen from Subimperial South Africa - Bond, Patrick (Africa Development, 2020)
African elites’ perpetual hope for export-led growth based on primary commodity extraction continues to suffer from harsh economic, political and now also climatic and public-health realities. Among the contradictions, COVID-19’s economic lockdown amplified two of the most difficult aspects of South Africa’s regional and inter-ethnic relations: increased working-class desperation as township economies suffered the most from the pandemic, and the inability to send remittances back home. Although new dimensions emerged during 2020 – e.g., mass social-media trolling, Cabinet ministers’ biases translated into legislation, and protests at African countries’ Pretoria embassies – there were indications well before COVID-19 that local hostility to the continent’s people would ratchet up, just as Cyril Ramaphosa took the African Union chair. Xenophobic upsurges regularly witnessed in Johannesburg suggest that this ongoing melting pot of African entrepreneurs suffers some of the continent’s most extreme political-economic contradictions. However, there are antidotes to top-down neoliberalism still emanating from the African Development Bank and World Economic Forum-Africa, some of which are potentially progressive, including unprecedented anti-authoritarian protests in at least 18 countries. But the first step is recognising just how much the official rhetoric, even from organic African elite sources, departs from reality.